'Stones from another mountain': an analysis of the cinematic significance of Hong Kong's Storm films in China's anticorruption campaign. Issue 1 (2nd January 2021) - Hung, Alvin Hoi-Chun
ABSTRACT: When Chinese leader Xi Jinping came to power in 2012, the Chinese government adopted an anticorruption policy pledging to uproot corruption in China, and since then, an anticorruption crime film series known as the Storm films has been produced in Hong Kong and released with a progressively successful box-office performance in mainland China. The purpose of this essay is to examine the series' role as an entertainment-based pedagogical and ideological tool within the broader socio-political context of post-2012 China. I argue that through portraying corruption in Hong Kong and the idealized role model image of anticorruption law enforcement officers, this Hong Kong film series has served to create a safe distance with which the general public in mainland China could be educated about the social harms of corruption, and could be forged with an 'appropriate' legal consciousness comprising complete trust, respect, and support for both the anticorruption campaign and the law itself.